1981
DOI: 10.1539/joh1959.23.606
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Using T & T Olfactometer which had been developed and standardized for clinical use in Japan recently, measurements of olfactory thresholds of odor detection and of odor recognition were carried out on 33 subjects (26 males and 7 females), who had worked in a chromate producing factory. The subjects had left the factory before 7 years or more. Five kinds of test odors were used; beta-phenyl ethyl alcohol, methyl cyclopentenolone, iso-valeric acid, gamma-undecalactone, and scatol. The degree of olfaction loss w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Increased oxidative stress, chromosome disruptions and DNA-adduct formation are some of the many cellular damages found to be caused by high level exposure to Cr in the brain ( Wise et al, 2022 ). While there are no neuroimaging studies investigating the impact of chromium exposure to date, previous studies in humans have observed evidence linking chromium exposure to neurological and psychiatric conditions, including olfactory dysfunction, autism spectrum disorder, and acute schizophrenia ( Watanabe and Fukuchi, 1981 ; Kitamura et al, 2003 ; Saghazadeh et al, 2020 ; Wise et al, 2022 ). These findings suggest an impact of chromium exposure on underlying neurobiological function.…”
Section: Discussionmentioning
confidence: 99%
“…Increased oxidative stress, chromosome disruptions and DNA-adduct formation are some of the many cellular damages found to be caused by high level exposure to Cr in the brain ( Wise et al, 2022 ). While there are no neuroimaging studies investigating the impact of chromium exposure to date, previous studies in humans have observed evidence linking chromium exposure to neurological and psychiatric conditions, including olfactory dysfunction, autism spectrum disorder, and acute schizophrenia ( Watanabe and Fukuchi, 1981 ; Kitamura et al, 2003 ; Saghazadeh et al, 2020 ; Wise et al, 2022 ). These findings suggest an impact of chromium exposure on underlying neurobiological function.…”
Section: Discussionmentioning
confidence: 99%
“…There are many studies about the prevalence of olfactory dysfunction in the general population, but few studies have investigated the prevalence of olfactory dysfunction in specific occupational groups. Watanabe and Fukuchi 28 conducted the olfactory function test in 33 workers in a chromate-producing factory, reporting that 54.5% exhibited olfactory dysfunction. Rose et al 29 examined 55 workers exposed to cadmium fumes in a brazing operation and reported that 56.4% exhibited olfactory dysfunction (43.6% mild hyposmia and 12.7% moderate or severe hyposmia).…”
Section: Discussionmentioning
confidence: 99%
“…i.Frequent olfactory impairment, atrophic nasal mucosa, nasal septal ulceration and sinusitis.Anosmia in 114/251 workers (46%) with chronic sinusitis; less severe loss of smell in other Ni-exposed workers.ChromiumSeeber et al 1976 [53]Chrome paint plant (manufacture of basic zinc chromate (zinc yellow))Values exceeded 0.1 CrO 3 air, and rose at certain points to up to 20 CrO 3 . More precise values are not stated.5 chronically exposed workers, 14 intermittently exposed workers (not longer than 2 h per day), 5 mask-wearing workers (wearing fine-dust filter masks for the full duration)9 office workers at the same company, 23 employees at hospitalTest with odour strips (6 different stimuli in 8 concentrations)Olfactory sensitivity of control group and non-exposed individuals substantially higher than that of exposed individuals.“Significant” relationship between chromium exposure and loss of olfaction.Chronically exposed individuals: damage to the nasal mucous membrane.Intermittently exposed group and workers with a mask: damage to the nasal mucous membrane only in a part.Seeber and Fikentscher 1980 [54]See aboveOccupational exposure “substantially reduced” by suitable measures (not specified)3 chronically exposed workers, 9 intermittently exposed workers (not longer than 2 h per day)4 mask-wearing workers (wearing fine-dust filter masks for the full duration)7 office workers at the same company,23 employees at hospitalSee aboveConfirmation of the relationship between the pathological nasal mucous membrane findings and olfactory dysfunction in 16 workers exposed to different levels.No improvement in the mucous membrane or olfaction. a Watanabe and Fukuchi (1981) [55]Chromate production plantAir Cr concentration of 20.17 according to [56]33T&T olfactometer (odour detection threshold and odour recognition)“Middle and high grade decrease of odor recognition faculty” in 18 workers (54.5%) including 2 anosmiac, one of whom also complained of a taste disorder.51% exhibited nasal septum perforations.Relation between degree of olfaction loss and duration of employment in the chromate producing factory. a Kitamura et al 2003 [56]Cr plating factoryAverage atmospheric concentration was 0.02282734T&T olfactometer (odour detection threshold and odour recognition)Olfactory perception threshold testNo significant differences for sensory and perception threshold.Significantly higher values for the odour recognition test than those for controls, positive correlation with duration of exposure.None of Cr workers showed nasal septum perforation or ulceration.Aiyer et al 2003Chromium plating industryN. i.28N.…”
Section: Industrial Chemicals With a Potential Impact Upon Olfactionmentioning
confidence: 99%